BADANIA KLINICZNE I DOŚWIADCZALNE W CHOROBACH SERCA, PŁUC I NACZYŃPreliminary ultrastructural investigations of cardiomyocytes from children with different types of congenital heart malformations - Tosik, Dariusz; Moll, Jacek; Moll, Jadwiga; Bartel, Hieronim; Kulig, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Introduce : We present ultrastructural investigations of cardiomyocytes of three types of heart congenital malformations. Aim : Characterization of ultrastructural changes in cardiomyocytes from three different heart malformations. Material and Methods : Tissue blocks were obtained during surgical correction of heart congenital malformations. Ultrastructural investigations were performed on three groups of patients. Their age varied from 11 days to 6.5 years. Ultrastructural changes of cardiomyocytes from the below mentioned congenital malformations were evaluated: ventricular septal defect (VSD), tetralogy of Fallot (TOF) and hypoplastic left heart syndrome (HLHS). The reference group was VSD. Results : In cardiomyocytes of the VSD group significant features of injury were not observed. In nuclei of cardiomyocytes of TOF and HLHS groups, morphological signs of apoptosis, such as nuclear shrinkage and marginal chromatin condensation, were observed. Mitochondria, on the other hand, were characterized by damages of a different degrees based on their oedema, matrix vacuolization and inner membranes injury. Abnormal configuration of myofilaments of cardiomyocytes’ sarcomeres in case of TOF and HLHS was also observed. Within intercalated disks deposition of electron dense substance was observed. Conclusions : Ultrastructural investigations indicate that the probable mechanism of cardiomyocyte injury in TOF and HLHS groups is closely connected with apoptosis activated in the mitochondrial pathway. Morphological changes of intercalated disks also suggest the possibility of injury of CAM proteins, responsible for normal organogenesis and forming the anchoring apparatus of myofilaments.